2020
DOI: 10.1039/c9se01242g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of simple carbazole-arylamine hole-transport materials for perovskite solar cells

Abstract: N,N-Dimethylamino-based carbazole-arylamine hole-transport materials show better performance than methylsulfanyl or methoxy counterparts in perovskite solar cells, and even exhibit higher efficiency and extremely lower laboratory synthesis cost than conventional spiro-OMeTAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 43 publications
0
24
1
Order By: Relevance
“…[43,47,48] The HTMs with large deposition amounts could increase hole migration distance due to growing thickness of the HTM layer, therefore, causing destructive device performance. Unlike one of our previous reports, [41] we noted that the variation trend of device performance has no connection with the concentration. The change trend of device performance does not change along with the concentration of HTMs.…”
Section: Chemistryselectcontrasting
confidence: 99%
See 1 more Smart Citation
“…[43,47,48] The HTMs with large deposition amounts could increase hole migration distance due to growing thickness of the HTM layer, therefore, causing destructive device performance. Unlike one of our previous reports, [41] we noted that the variation trend of device performance has no connection with the concentration. The change trend of device performance does not change along with the concentration of HTMs.…”
Section: Chemistryselectcontrasting
confidence: 99%
“…The deposition amount of HTMs has been proved to have a remarkable effect on PSCs' performance. [41] The solubility of these molecules are measured in chlorobenzene, the obtained results are listed in Table S1, the investigated molecules exhibit good solubility, except O-4,6. We preliminarily used these molecules in devices with varying concentrations.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Similarly, Chen et al investigated carbazole-based HTM with diphenylamine substitution at the 1,3,6,8 positions, which showed PCE of 17.8% . Many other research groups studied carbazole-triarylamine/diarylamine connected via a phenyl, biphenyl, triphenylamine, and dibenzofuran core as HTMs for PSC. In addition, isomeric carbazole-triarylamine based HTMs have been reported to result in different photovoltaic performances by altering the substitution position at the carbazole core. For instance, Li et al demonstrated that 2,7-difunctionalized carbazole exhibit superior PCE than the corresponding 3,6-difunctionalized carbazole . However, tetra-substituted isomeric carbazoles as HTMs are scarcely investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Carbazole and fluorene chromophores are among the most popular structural building blocks, used for the construction of the organic HTMs. [ 25–30 ] In a recent work, it was shown that the replacement of the methoxyphenyl fragment of the popular HTM Spiro‐OMeTAD with the 9,9‐dimethylfluorenyl chromophore led to the superior performance. [ 31 ] Such an increase in the efficiency and stability was attributed to the optimized thermal properties, as well as beneficial alignment of the energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Carbazole and fluorene chromophores are among the most popular structural building blocks, used for the construction of the organic HTMs. [25][26][27][28][29][30] In a recent work, it was shown that the replacement of the methoxyphenyl fragment of the popular HTM Spiro-OMeTAD with the 9,9-dimethylfluorenyl chromophore led to the superior performance. [31] Such an increase in New Spiro-OMeTAD analogues and the simpler "half" structures with the terminated methoxyphenyl and/or carbazolyl chromophores are successfully synthesized under Hartwig-Buchwald amination conditions using commercially available starting materials.…”
Section: Introductionmentioning
confidence: 99%